Selected Studies of Jan Gonda, Volume 6 Selected Studies, part 2 : Presented to the author by the Department of Indology, Utrecht University - Gonda, (Asian Studies - Book Archive pre-2000., 1991)
The print edition is available as a set of two volumes (9789004094468).